2021
DOI: 10.2478/vjbsd-2021-0008
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Innovation on Small and Medium Enterprises: A Bibliometric Analysis

Abstract: Innovation plays great role in organizational competitiveness and sustainable business processes and it should be a key success policy for small and medium-sized enterprises (SMEs) all over the world. To this effect, the purpose of this study is to present a comprehensive understanding of the scientific studies made on the field of innovation and its effect on small and medium enterprises performance. A bibliometric study was used to analyze articles published between 1976 and 2020 and create an illustrative m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 64 publications
2
8
0
Order By: Relevance
“…Therefore, it is concluded that the proposed Hypothesis (H1) is supported by the research results. These results are supported by a study conducted in Ghana [86] which found a significant positive relationship between innovation, proactiveness, and profitability. Additionally, in their study of 94 Turkish manufacturing foreign direct investment (FDI) firms, [87] found that two dimensions of entrepreneurial orientation, innovation and proactiveness, positively and significantly affected the performance of the firms.…”
Section: Results Of Inferential Statistics Correlationssupporting
confidence: 68%
“…Therefore, it is concluded that the proposed Hypothesis (H1) is supported by the research results. These results are supported by a study conducted in Ghana [86] which found a significant positive relationship between innovation, proactiveness, and profitability. Additionally, in their study of 94 Turkish manufacturing foreign direct investment (FDI) firms, [87] found that two dimensions of entrepreneurial orientation, innovation and proactiveness, positively and significantly affected the performance of the firms.…”
Section: Results Of Inferential Statistics Correlationssupporting
confidence: 68%
“…Moreover, recent studies have recommended that more countries collaborate in their research on SME innovation to share the resulting benefits and costs [66]. Accordingly, the results of the analysis showed much cooperation among the different clusters, but also the USA and the People's Republic of China collaborated in one cluster, the collaboration of England, Germany, Italy, and France in the second cluster, Spain, Brazil, and Sweden collaborating in another cluster, while Australia, Malesia and Pakistan also collaborate in other clusters.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…The bibliometric analysis examines the bibliographic data quantitatively, thus offering an overview of some research fields in accordance with adequate indicators, whereas through some other methods, such as a systematic literature review, the most relevant articles may be selected and analyzed more closely [65]. The main indicators which this approach uses to identify top trends include the publications number, the citations number, the most relevant authors, and the most influential research institutions and countries [66].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(5) The information asymmetry of SaMSE and financial institutions, their corporate credit information and the personal credit information data of business owners are not optimistic, and the acquisition of their credit information data is difficult to reflect through the current official query system [9][10].…”
Section: Main Credit Risk Characteristicsmentioning
confidence: 99%